Discover the best answers at Westonci.ca, where experts share their insights and knowledge with you. Explore thousands of questions and answers from a knowledgeable community of experts on our user-friendly platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
y - y₁ = m(x - x₁)
y - (-4) = 1(x - (-1))
y + 4 = 1(x + 1)
y + 4 = 1(x) + 1(1)
y + 4 = -x + 1
- 4 - 4
y = -x - 3
y - (-4) = 1(x - (-1))
y + 4 = 1(x + 1)
y + 4 = 1(x) + 1(1)
y + 4 = -x + 1
- 4 - 4
y = -x - 3
We hope our answers were helpful. Return anytime for more information and answers to any other questions you may have. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.